Assessing Insulin Sensitivity and Postprandial Triglyceridemic Response Phenotypes With a Mixed Macronutrient Tolerance Test - Newman, John W.; Krishnan, Sridevi; Borkowski, Kamil; Adams, Sean H.; Stephensen, Charles B.; Keim, Nancy L. (Frontiers in Nutrition, 2022)
The use of meal challenge tests to assess postprandial responses in carbohydrate and fat metabolism are well established in clinical nutrition research. However, challenge meal compositions and protocols remain variable. Here we validate a mixed macronutrient tolerance test (MMTT) containing 56 g palm oil, 59 g sucrose and 26 g egg white protein for the parallel determination of insulin sensitivity and postprandial triglyceridemia in clinically healthy subjects. The MMTT was administered in two study populations. In one, women with overweight/obese BMIs (n =43) involved in an 8wk dietary intervention were administered oral glucose tolerance tests (OGTTs) and MMTTs within 2 d of each other after 0, 2, and 8wk of the dietary intervention. In the other, 340 men and women between 18 and 64 y of age, with BMI from 18-40 kg/m2 completed the MMTT as part of a broad nutritional phenotyping effort. Postprandial blood collected at 0, 0.5, 3, and 6h were used to measure glucose, insulin, and clinical lipid panels. The MMTT postprandial insulin-dependent glucose disposal was evaluated by using the Matsuda Index algorithm and the 0 and 3 h blood insulin and glucose measures. The resulting MMTT insulin sensitivity index (ISIMMTT) was strongly correlated (r = 0.77, p <0.001) to the OGTT-dependent 2 h composite Matsuda index (ISIComposite), being related by the following equation: Log (ISIComposite) = [0.8751 x Log(ISIMMTT)] – 0.2115. An area under the triglyceride excursion curve >11.15 mg/mL h 1 calculated from the 0, 3 and 6h blood draws established mild to moderate triglyceridemia in agreement with ~20% greater prevalence of hypertriglyceridemia than fasting indications. We also demonstrate that the product of the 0 to 3 h and 3 to 6 h triglyceride rate of change as a function of the triglyceride incremental area under the curve optimally stratified subjects by postprandial response patterns. Notably, ~2% of the population showed minimal triglyceride appearance by 6 h, while ~25% had increasing triglycerides through 6 h. Ultimately, using three blood draws the MMTT allowed for the simultaneous determination of insulin sensitivity and postprandial triglycerideimia in individuals without clinically diagnosed disease.